2021
DOI: 10.3390/pathogens10010070
|View full text |Cite
|
Sign up to set email alerts
|

Enlisting the Ixodes scapularis Embryonic ISE6 Cell Line to Investigate the Neuronal Basis of Tick—Pathogen Interactions

Abstract: Neuropeptides are small signaling molecules expressed in the tick central nervous system, i.e., the synganglion. The neuronal-like Ixodes scapularis embryonic cell line, ISE6, is an effective tool frequently used for examining tick–pathogen interactions. We detected 37 neuropeptide transcripts in the I. scapularis ISE6 cell line using in silico methods, and six of these neuropeptide genes were used for experimental validation. Among these six neuropeptide genes, the tachykinin-related peptide (TRP) of ISE6 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…TK immunoreactivity was observed in the synganglion and in the ducts of the salivary glands of R. appendiculatus (Šimo et al 2009a ) and a precursor encoding IscapTKs has been identified in the genome of I. scapularis (Šimo et al, 2014 ). Furthermore, infection of the ISE6 tick cell line with A. phagocytophilum led to strain-dependent changes in the TK expression (Mateos-Hernández et al 2021 ). Possible involvement of TKs in the tick-pathogen interactions make them even more interesting as neuropeptides for future studies.…”
Section: Neuropeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…TK immunoreactivity was observed in the synganglion and in the ducts of the salivary glands of R. appendiculatus (Šimo et al 2009a ) and a precursor encoding IscapTKs has been identified in the genome of I. scapularis (Šimo et al, 2014 ). Furthermore, infection of the ISE6 tick cell line with A. phagocytophilum led to strain-dependent changes in the TK expression (Mateos-Hernández et al 2021 ). Possible involvement of TKs in the tick-pathogen interactions make them even more interesting as neuropeptides for future studies.…”
Section: Neuropeptidesmentioning
confidence: 99%
“…R. appendiculatus (Šimo et al 2009a) Small neurons in the synganglion, innervation of SG type II acini from the neurons OsSG1,2 (Šimo et al 2009a, b) Currently unknown function Myoinhibitory peptide (MIP) R. appendiculatus (Šimo et al 2009a) I. scapularis (Šimo et al 2009b, 2014) Neurons in the synganglion, innervation of the SG acini type II, III by PcSG neuron (Šimo et al 2009a, b), innervation of the rectal sac from PoHG1,2 neurons (Šimo et al 2013, 2014) SIFamide antagonist-reduces SIFα-activated hindgut motility Tachykinin (TK/TK-like) R. appendiculatus (Šimo et al 2009a) I. scapularis (Mateos-Hernández et al 2021) Neurons in the synganglion which innervate its surface (Šimo et al 2009a), and ducts in salivary glands (Mateos-Hernández, et al 2021) Currently unknown function SIF amide (SIFa) R. appendiculatus (Šimo et al 2009a) I. scapularis (Šimo et al 2009b, 2014) Peptidergic neurons in the synganglion, innervation of the SG acini type II and III by PcSG neuron (Šimo et al 2009a, b), innervation of the rectal sac from PoHG1,2 neurons (Šimo et al 2013, 2014) MIP antagonist, stimulates hindgut activity Insulin-like peptide (ILP)…”
Section: Allatostatin Amentioning
confidence: 99%
“…A. phagocytophilum ) can partially mirror that of tick tissues such as midgut and salivary glands ( Cabezas-Cruz et al., 2017a , b ). In fact, some functional and morphological features of tick tissues have been described in tick cell lines ( Oliver et al, 2015 ; Mateos-Hernández et al., 2021b ). Changes in the abundance of several enzymes involved in carbohydrate metabolism (e.g.…”
Section: Tick Cells As a Tool To Measure Evolutionary Interactions Be...mentioning
confidence: 99%
“…In ticks, a group of haematophagous arthropods belonging to the Chelicerata, the CNS is a specialized organ called a synganglion 2 , organized as a single mass of cells. As ticks are potential transmitters of many pathogens and parasites, a better knowledge of the function of this essential organ could help in understanding interactions between ticks and tick-borne-pathogens 3 , but also provide targets for chemical acaricides 4 . Indeed, to-date, most acaricides have targeted neural functions, but as with many insect pests, the continued use of these molecules has generated resistance, prompting the need to find new methods or targets 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, in these data sets, it is impossible to assess the extent to which these gene collections were synganglion specific, as expression levels were only measured for synganglion samples, and were not compared to other tissues or the whole body. Recently, the Ixodes scapularis ISE6 cell line was shown to have neuronal characteristics, which provided a base for investigating neuronal interactions between ticks and pathogens 3 .…”
Section: Introductionmentioning
confidence: 99%